Direct Costs of Healthcare for Children with Type 1 Diabetes Using a CGM System: A Health Economic Analysis of the VIDIKI Telemedicine Study in a German Setting - Frielitz, Fabian Simon; Eisemann, Nora; Werner, Kristin; Hiort, Olaf; Katalinic, Alexander; Lange, Karin; von Sengbusch, Simone (Experimental and Clinical Endocrinology & Diabetes, 2022)
Aims The Virtual Diabetes Outpatient Clinic for Children and Adolescents (VIDIKI) study was a 6-month quasi-randomized, multicentre study followed by an extension phase to evaluate the effects of monthly video consultations in addition to regular care. A health economic analysis was conducted to assess the direct costs.Methods The cost data of 240 study participants (1–16 years of age) with type 1 diabetes who were already using a continuous glucose monitoring system were collected in the first 6 months of the study. The intervention group (IG) received monthly video consultations plus regular care, and the waiting control group (WG) received only regular care. Cost data were collected for a comparable anonymized group of children from the participating health insurance companies during the 6-month period before the study started (aggregated data group [AG]).Results Cost data were analysed for the AG (N=840) 6 months before study initiation and those for the study participants (N=225/240). Hospital treatment was the highest cost category in the AG. There was a cost shift and cost increase in the IG and WG, whereby diabetes supplies were the highest cost category. The mean direct diabetes-associated 6-month costs were € 4,702 (IG) and € 4,936 (WG).Conclusion The cost development within the cost collection period over two years possibly reflects the switch to higher-priced medical supplies. Video consultation as an add-on service resulted in a small but nonsignificant reduction in the overall costs.
Keywords: Health economics; costs; CGM; telemedicine; type 1; diabetes; children